2020
DOI: 10.3390/ijerph17051707
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Plantar Pressures with Wear of a Running Shoe

Abstract: Running shoes typically have a lifespan of 300–1000 km, and the plantar pressure pattern during running may change as the shoe wears. So, the aim of this study was to determine the variation of plantar pressures with shoe wear, and the runner’s subjective sensation. Maximun Plantar Pressures (MMP) were measured from 33 male recreational runners at three times during a training season (beginning, 350 km, and 700 km) using the Biofoot/IBV® in-shoe system (Biofoot/IBV®, Valencia, Spain). All the runners wore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…This type of foot, with a higher arch, presents less plantar load due to having less contact with the ground (Burns et al, 2005;Anbarian and Esmaeili, 2016), as has also been seen in this study. Also, and in line with other running studies (Willems, De Ridder and Roosen, 2012;Anbarian and Esmaeili, 2016;Escamilla-Martínez et al, 2020), the greatest loads were observed in the forefoot and rearfoot regions due to their importance in the initial contact and propulsion phases of running gait (Escamilla-Martínez et al, 2020).…”
Section: 1relationship Between Plantar Pressure and Temperaturesupporting
confidence: 89%
See 1 more Smart Citation
“…This type of foot, with a higher arch, presents less plantar load due to having less contact with the ground (Burns et al, 2005;Anbarian and Esmaeili, 2016), as has also been seen in this study. Also, and in line with other running studies (Willems, De Ridder and Roosen, 2012;Anbarian and Esmaeili, 2016;Escamilla-Martínez et al, 2020), the greatest loads were observed in the forefoot and rearfoot regions due to their importance in the initial contact and propulsion phases of running gait (Escamilla-Martínez et al, 2020).…”
Section: 1relationship Between Plantar Pressure and Temperaturesupporting
confidence: 89%
“…One explanation for this distribution could be provided by the usual distribution of the materials of the running shoes. Cushioning systems usually predominate in midfoot and rearfoot (Escamilla-Martínez et al, 2020), which may create an insulating effect. However, this idea is speculation, as each participant used their own footwear, and no control of the characteristics of the materials was undertaken.…”
Section: 2sole Of the Foot Or Footwear Outsole Temperaturementioning
confidence: 99%
“…The area where the temperature increased least was the medial midfoot, where there was an increase of around 3°C after the exercise (Tables 2 and 3). This greater increase in temperature in the lesser toe area may be due to the fact that this area starts from a lower initial temperature, due to greater rubbing in the shoes, or because of the biomechanical involvement of this area during the take-off phase in the run [21].…”
Section: Discussionmentioning
confidence: 99%
“…BioFoot ® is an in-shoe system developed in 2001 by Biomechanics Institute of Valencia, Spain. The system is equipped with 64 piezoelectric sensors and can acquire samples with a sampling rate ranging from 50 Hz to 250 Hz [ 111 ]. It is provided with a wireless connection (11 Mbs), and data can be sent to and logged by a computer [ 112 ].…”
Section: Description Of Proposed Methods Using Other In-shoe Systementioning
confidence: 99%
“…It is provided with a wireless connection (11 Mbs), and data can be sent to and logged by a computer [ 112 ]. Recently, it was used in a study to determine the correlation between the plantar pressure variation, the shoe wear, and the comfort of runners with the same type of shoes [ 111 ].…”
Section: Description Of Proposed Methods Using Other In-shoe Systementioning
confidence: 99%